Endless Pressure: Life on a Low Income in Austere Times. (19th June 2016) - Pemberton, Simon; Fahmy, Eldin; Sutton, Eileen; Bell, Karen
Abstract: Much has been written that details the decline in living standards following the 'credit crunch' in the UK. It remains that we understand to a lesser degree the lived reality of poverty through the Great Recession and into the era of austerity. This article draws on testimonies of 62 participants from low income households conducted in three different areas of the UK during 2012–13 to document the pressures that this period brought to bear on these households. According to these testimonies, the experience of poverty intensified in key respects: first, participants reported feeling, more than ever before, that they were 'existing, rather than living' due to the meagre budgets they were forced to live on; second, the precarious nature of work and social security contributed to a sense of insecurity that was all pervasive in our participants' lives; third, due to the pejorative political rhetoric and media coverage of poverty, our participants felt that their lives were placed under increased scrutiny which deleteriously impacted their wider relationships and sense of belonging. Our analysis demonstrates the profound consequences for those living on low incomes of the continued shift to residual forms of state welfare and the increased reliance on the 'Big Society' as a means to deal with the pressures identified in this article.